STRATEGI PENINGKATAN NILAI PERUSAHAAN MELALUI PERAN MODERATOR PROFITABILTAS DAN SIZE - Dhurotus Sangadah Sangadah (Universitas Gajayana Malang, 2021)
This study aims to examine and analyze the positive & negative impacts of the Covid-19 pandemic on the sectoral index on the IDX. This study uses a case study method with a quantitative analysis approach, descriptive exploratory, and uses historical data on sectoral stock indices with purposive sampling technique. In the form of IDX secondary data, from December 2, 2019 to December 30, 2020. The study population was 10 IDX sectoral indexes. The research period from December 2, 2019 to December 30, 2020 was analyzed using the Chartnexus analysis tool based on the performance of the stock sectoral index. The results of the study concluded that: biggest positive and negative impacts of the Covid -19 pandemic on the Sectoral Index on the IDX for the period 30 December 2019 to 30 December 2020, namely a positive impact on the Mining Sector Index an increase of +531.06 (+ 37%), Agri +151.77 (+11.3%), while a negative impact occurred decrease in the Consumer sector by -306.99 (-14.2%), Misc-Ind -125.88 (-10.1%) . Keywords : Positive & Negative Impacts of the Covid-19 Pandemic, 10 Sectoral Index Performance.